The biological side of randomness - Ciulla, Michele M (PeerJ PrePrints, 2015)
This is my comment to an article that was recently published by Science (see ref.1) raising several issues. In this brief note I will not address the methodological issue, as the main merit of the article is to have questioned the preventive medicine as a strategy by undermining its foundations with the randomness of disease, in this case, the cancer. To understand the scope of this refutation we must remember that the preventive strategy was developed since the introduction of the concept of risk factor, that date back to the Framingham Heart Study (FHS) started in 1948. Indeed, prior to the FHS, doctors were still engaged in the study of causation by following the established paradigm of aetiology, and had not yet focused on the concept of prevention or prophylaxis. After having metabolised the concept of risk factor for disease and having made prevention of risk factors the main strategy to fight multifactorial diseases for years, today, in a Western world that is aging, we are facing a new challenge since prevention seems to be no longer enough to cope with diseases such as cancer and, possibly, we need new strategies that we still have not. And this why? Possibly because the randomness appears ever more like the engine that drives the physical universe even if, for living organisms, we must admit several deterministic or, at least, very reproducible events since they are able to actively interact with the environment.
Keywords: preventive medicine; randomness; risk factors; cancer; disease; chaos; adaptability; environment; genetic program; stem cells